PENGARUH NILAI SOLA SCRIPTURA DALAM HURIA KRISTEN BATAK PROTESTAN PADA ARSITEKTUR TRADISIONAL BATAK TOBA - , CHANDRA SIAGIAN; , Dra. Sonjoruri B. Trisakti, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Lutheran Christians underlying HKBP is the largest religion practiced by the Batak Toba society. Lutheran Christian denominationis also the most influencing cultural developments within Batak Toba society. The purpose of this research is to describe, analyze, and explain the HKBP that influence within the traditional architecture Batak Toba. This study applies the axiology study of science to explain the effect of HKBP value on the scientific aspects of Batak Toba traditional architecture with qualitative method supported by the review of literature and field data. Literature review is used to discuss the external factors of valueswithin science in the axiology of science as a formal object and Batak Toba traditional architecture as a material object. Field datum are used to emphasize the elaboration of Batak Toba traditional architecture as amaterial object. The methodical element in this researchis the description, interpretation and holistica. Like the other church of other Lutheran denominations, HKBP also bases its view on the principle of Sola Scriptura which does not recognize the truth of Christ outside the Bible. According this research it is concluded that the effect of HKBP that happened in Batak Toba traditional architecture took the form of changes in the usability aspects of rumaâs spatial arrangement. Changes have taken place in the room that were directly associated with aspect of the cult of Mulajadi Na Bolon and ancestors and were deemed a sin compatible with the values of Sola Scriptura in HKBP. Moreover changes also occur because of European style health and efficiency aspects which take precedence in the building process of new shelters by the Toba Batak Christian family.